T-ABSO T-Abso and T-Abso Quasi Primary Fuzzy Submodules - Hanoon, Wafaa H.; Khalaf, Hatem Y. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
Let á¸¾ be a unitary R-module and R is a commutative ring with identity. Our aim in this paper  to study the concepts T-ABSO fuzzy ideals, T-ABSO fuzzy submodules and T-ABSO quasi primary fuzzy submodules, also we discuss these concepts in the class of multiplication fuzzy modules and relationships between these concepts. Many new basic properties and characterizations on these concepts are given.